The impact of migrant work experience on rural households’ participation in digital finance: Evidence from China - Fan Xu; Xiaolei Zhang; Lezhu Zhang (PLoS ONE, 2025)
Currently, the development of digital finance in China’s rural areas remains in its early stages. The proportion of rural households participating in digital finance and the types of participation are relatively low. This hinders the realization of digital finance’s inclusive effects. This paper examines the influence of migrant work experience on participation in digital financial of rural households using data from the China Household Finance Survey (CHFS). The findings suggest that migrant work experience significantly increases the probability of rural households’ digital financial participation and increases the breadth of participation. Heterogeneity analysis finds that migrant work experience promotes digital financial participation more for rural households with migrant formal work experience, migrant entrepreneurial experience, completion of compulsory education, and long-tail groups. Mechanism analysis finds that migrant work experience can influence rural households’ digital financial participation by improving their financial literacy and broadening their social networks.